Safeguarding grain with gas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Insect pests can quickly turn grain stocks into a pile of dust, and to prevent this happening methyl bromide has been used for many years to fumigate grain. Although this gas is an excellent fumigant, it is now known to be one of the causative...